1993
DOI: 10.1111/j.1570-7458.1993.tb00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimetabolic effects of plant lectins and plant and fungal enzymes on the nymphal stages of two important rice pests, Nilaparvata lugens and Nephotettix cinciteps

Abstract: Insect feeding trials were carried out to determine the effects of incorporating a range of plant derived proteins into artificial diets fed to leafhopper and planthopper pests of rice. The lectins Galanthus nivalis agglutinin (GNA) and wheat germ agglutinin (WGA), and the enzyme soy bean lipoxygenase (LPO) were shown to exhibit significant antimetabolic effects towards first and third instar nymphs of rice brown planthopper (Nilaparvata lugens Stål) when incorporated into artificial diet at 0.1% (w/v), 0.1% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
113
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(122 citation statements)
references
References 16 publications
6
113
3
Order By: Relevance
“…Recently, such a mechanism of GNA toxicity to BPH has been confirmed . In our studies, the expression of GNA in transgenic rice caused similar insecticidal effects to those of GNA fed to BPH and GLH in artificial diets (Powell et al, 1993), with decreased feeding as well as decreased insect survival (Figures 6 and 7). Marked decreases in the honeydew production of both BPH (80.08%) and GLH (69.06%) insects were observed when fed on T 2 homozygous plants ( Figure 6), thus suggesting the high feeding deterrent effect of GNA against both the insects.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Recently, such a mechanism of GNA toxicity to BPH has been confirmed . In our studies, the expression of GNA in transgenic rice caused similar insecticidal effects to those of GNA fed to BPH and GLH in artificial diets (Powell et al, 1993), with decreased feeding as well as decreased insect survival (Figures 6 and 7). Marked decreases in the honeydew production of both BPH (80.08%) and GLH (69.06%) insects were observed when fed on T 2 homozygous plants ( Figure 6), thus suggesting the high feeding deterrent effect of GNA against both the insects.…”
Section: Discussionmentioning
confidence: 71%
“…Two major homopteran pests, rice brown planthopper (Nilaparvata lugens) and rice green leafhopper (Nephotettix virescens) cause severe physiological damage to the rice plant, as well as acting as vectors for rice tungro virus, grassy stunt virus, and ragged stunt virus (Mochida et al, 1979;Saxena and Khan, 1989). Earlier investigations (Powell et al, 1993) indicated that the snowdrop-lectin protein (GNA), which was isolated from the ornamental monocotyledonous plant, Galanthus nivalis (snowdrop), belonging to Amarillidaceae family, is toxic to sap-sucking insects of rice. Furthermore, it was reported that the snowdrop-lectin gene (gna), which is expressed in japonica rice (Rao et al, 1998) and wheat (Stoger et al, 1999), conferred resistance against rice brown planthopper and grain aphid, respectively.…”
Section: Among the Available Genetic Transformation Methodsmentioning
confidence: 99%
“…Five third instar nymphs of N. lugens were refolded on the column by gradually removing the denaturant. removed from the host plant using a fine paintbrush to minimise The protein was eluted in 300 mM imidazole and diluted to physical damage, and placed in a plastic feeding chamber [24]. 100 µg/ml in 50 mM Tris/HCl pH 7.9.…”
Section: Resultsmentioning
confidence: 99%
“…The insecticidal activity of Man-binding lectins has been demonstrated against a spectrum of insects, both in artificial diets supplemented with the lectins (Powell et al, 1993;Fitches et al, 2001) and also when insects feed on natural and transgenic plants expressing lectins (Gatehouse et al, 1996;Nagadhara et al, 2004;Sadeghi et al, 2008). The snowdrop lectin, GNA, is toxic to brown planthopper (Nilaparvata lugens; Powell et al, 1998;Tang et al, 2001) and tomato moth (Lacanobia oleracea) larvae (Fitches et al, 1997;Gatehouse et al, 1997Gatehouse et al, , 1999 as well as to several aphid species (Hilder et al, 1995;Rahbé et al, 1995;Gatehouse et al, 1996;Sauvion et al, 1996).…”
mentioning
confidence: 99%
“…The insecticidal activity is attributed to lectin recognition of Man glycans in the digestive tracts of insects (Fitches et al, 2001;Majumder et al, 2004). Immunohistochemical studies show that these lectins bind to carbohydrate moieties of glycoproteins on epithelial cells lining the luminal surface of insect midguts, such as the binding of GNA in brown planthopper (Powell et al, 1993(Powell et al, , 1998 and concanavalin A in pea aphids (Acyrthosiphon pisum; Sauvion et al, 2004). An additional target is the peritrophic matrix lining the midgut region.…”
mentioning
confidence: 99%